Companies’ vision, mission, and core values focus on human resource management - Akter, Sraboni (Goodwood Publishing, 2021)
Purpose: This study aimed to determine companies’ vision, mission, and core values focus on human resource management. Research methodology: This study used qualitative method and 14 companies’ website has been used to identify their mission, vision and core values. Results: From the total of 14 FMCG companies that had been used in this study only five (Akij group, Marco Bangladesh Reckitt Benckiser Group plc (RB), Eskayef Pharmaceuticals Ltd, and Danish) of them showed that they have no mention about the human resource management and nine of them showed their concern towards human capital in their vision, mission, and core values. Limitation: This study is only confined to identify the mission, vision, core values, not their impact. Besides that, it is only limited to the small number of FMCG companies in Bangladesh. Contribution: This study’s results contribute to understanding the importance of focusing on human resource management on the companies’ vision and mission and explaining the reason for modifying the existing statements.